PENGARUH KOMPRES HANGAT PAYUDARA TERHADAP KECUKUPAN ASI BAYI PADA IBU POST PARTUM DI NAGARI KOTO PADANG WILAYAH KERJA PUSKESMAS KOTO BARU TAHUN 2025 - Putri Nurul Aini; Evin Noviana Sari; Sri Andar Puji Astuti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Providing sufficient and quality breast milk is very important for the health and growth of infants, especially in the postpartum period. One alternative to increase the production and release of breast milk non-pharmacologically is by applying warm compresses to the breasts. This study aims to determine the effect of warm breast compresses on the adequacy of breast milk in postpartum mothers in Nagari Koto Padang, Koto Baru Health Center Working Area. The method used is quantitative with a pre-experimental one group pretest-posttest design. The sample size was 10 people, selected using a purposive sampling technique. Measurement of breast milk adequacy was carried out through a questionnaire before and after the intervention. The results of the study showed that the average decreased to 1.40, meaning that there was a decrease in the level of breast milk insufficiency after the intervention. Statistical tests with Wilcoxon showed a P value = 0.003 (0.05), which means that the decrease was statistically significant. It can be concluded that warm breast compresses have a real effect in helping to ensure adequate breast milk supply in postpartum mothers and have been proven to significantly help to ensure adequate breast milk supply, so they can be used as an alternative non-pharmacological management. Keywords: warm compress, breast milk, breast milk adequacy, postpartum mother, baby